A quantitative systematic review of the effects of training interventions on enhancing the competence of nursing staff in managing challenging patient behaviour. (7th July 2017) - Tölli, Sirpa; Partanen, Pirjo; Kontio, Raija; Häggman‐Laitila, Arja
Abstract: Aims: This systematic quantitative review identifies and summarizes the current knowledge and effects of training interventions for managing patients' challenging behaviour. Background: Challenging behaviour is an acknowledged worldwide healthcare problem and its management can have a huge impact on quality of care. Evidence‐based training interventions that focus on managing challenging behaviour are needed, but few tools for the systematic evaluation of these interventions are currently offered. Design: A quantitative systematic review following the 2008 Centre for Reviews and Dissemination guidelines. Data Sources: CINAHL, Scopus, PsycInfo, PubMed and Cochrane were searched using the same terms for papers published in English from 2005–2015. Review Methods: Studies were assessed for quality and risk of bias, according to the Cochrane Effective Practice and Organisation of Care Group criteria. A narrative summary was conducted. Results: We included 17 studies and evaluated 16 training interventions. Interventions were classified into four key themes: disengagements, communication, controlling behavioural symptoms and restrictive measures. Our review showed that interventions were more likely to decrease violent incident rates and increase staff confidence than change staff attitudes or increase knowledge. The elements of competence used to manage challenging behaviour were measured unilaterally. The evidence provided by studies was largely weak. Conclusion: The variety of measurements used in the studies made comparing the effectiveness of the training interventions difficult. An individual's competence to manage challenging behaviour needs to be defined and a comprehensive scale for evaluating competence is also needed. Patient safety should be included in future evaluations.